UTERINE FIBROIDS AND THE CORRELATION WITH BLACK WOMEN: A GENETIC AND SOCIAL PERSPECTIVE - Pedro do Valle Varela, João; Nogueira Domingues, Shayenne; Quimquim Samuel, Andressa; Monfradini da Silva, Jacqueline; Corrêa de Melo, Lucas; Sasso Diniz, Mariana; Lorenzutti Teixeira, Gustavo; Spinassé Del Caro, Elisa; Cavaglieri Trevelin, Erick; Luiz Teixeira Fully, Fabio (Health and Society, 2024)
Uterine fibroids are common benign tumors in the uterus of women of reproductive age and can cause symptoms such as heavy menstrual bleeding, pelvic pain and increased abdominal volume. Studies have shown a higher prevalence of uterine fibroids in black women compared to women of other ethnicities. Understanding the causes of this disparity is fundamental to developing more effective prevention and treatment strategies. Investigating the relationship between the incidence of uterine fibroids and black ethnicity, analyzing the genetic and social factors that may contribute to this correlation and proposing measures to reduce the incidence of uterine fibroids in black women are the aims of this study. This is a systematic literature review using an exploratory and narrative method, with qualitative and quantitative premises. The databases used were PubMed, Scielo, Scopus, Web of Science and the Virtual Health Library. The articles analyzed were selected by exclusion and inclusion criteria, which are set out here, using the health sciences descriptors “uterine fibroids”, “black women and uterine fibroids”, “genetic factors and uterine fibroids” and “environmental factors and uterine fibroids”, reaching a total of 617 articles searched and 9 used in this study. Genetic studies have suggested a genetic predisposition to the development of uterine fibroids in black women, with the identification of genetic variants associated with a higher risk. In addition, social factors such as limited access to quality healthcare, socioeconomic inequalities and exposure to psychosocial stressors may also play an important role. Lack of access to preventive healthcare and unequal access to effective treatments may contribute to a higher prevalence of uterine fibroids in black women. Measures to reduce this disparity include promoting equitable access to healthcare, reproductive health education and public policies that address the underlying causes of health inequalities. The correlation between uterine fibroids and black women highlights the need for integrated approaches that consider both genetic and social factors. Promoting equity in access to health care and implementing public policies aimed at women’s health are key to reducing the incidence of uterine fibroids and improving the quality of life of black women.